Hiv Pada Ibu Hamil - Danarko, Ian; Mulyono, Eddy; Fahmi Rachmatullah (Universitas Pahlawan Tuanku Tambusai, 2024)
HIV infection in pregnant women is a significant issue in the global healthcare arena due to its serious impact on the health of both the mother and the unborn baby. This research aims primarily to explore the consequences of HIV infection in pregnant women, particularly in the context of virus transmission to the baby during pregnancy and childbirth. Additionally, this study focuses on preventive measures that can be implemented during pregnancy to reduce the risk of HIV transmission from mother to child. The research will investigate methods for preventing vertical transmission of HIV, such as antiretroviral therapy (ART) for pregnant women, surgical interventions (if necessary), as well as the management and monitoring of pregnant women living with HIV. Furthermore, the crucial role of mental health support for pregnant women with HIV will also be considered, given the psychological impact that may arise from this condition. The results of this research can provide deeper insights into the management of HIV in pregnant women and effective prevention measures, thus contributing to improving the health of both mothers and babies and reducing the transmission of the HIV virus to the next generation.